(untitled) (The Research of Medical Science Review, 2025)
Due to lack of proper and rapid identification of responsible pathogens, broad spectrum antibiotics are being overused in critically ill patients which are additional dilemma to development of antimicrobial resistance. The current study was conducted to perform antimicrobial susceptibility of positive blood culture by disk diffusion method and focused on reducing the 18 to 24 h of incubation interval to 6 hours and comparison of this result with standard disk diffusion testing performed on standard 24 hours growth. Antimicrobial susceptibility testing of identified isolates was performed as per guidelines on Muller Hinton agar plates. The susceptibility plates were examined at two intervals, first after 6 hours of incubation then after 24 hours of incubation and susceptibility results of isolates were noted and compared.